Effect of MHC haplotype on immune response upon experimental SHIVSF162P4cy infection of Mauritian cynomolgus macaques. - Alessandra Borsetti; Flavia Ferrantelli; Maria T Maggiorella; Leonardo Sernicola; Stefania Bellino; Alessandra Gallinaro; Stefania Farcomeni; Edward T Mee; Nicola J Rose; Aurelio Cafaro; Fausto Titti; Barbara Ensoli (PLoS ONE)
Little is known about the effects of Major Histocompatibility Complex (MHC) haplotypes on immunity to primate lentiviruses involving both acquired and innate immune responses. We present statistical evidence of the influence of MHC polymorphism on antiviral immunity of Mauritian cynomolgus macaques (MCM) following simian/human immunodeficiency virus SHIVSF162P4cy infection, involving the production of pro- and anti-inflammatory cytokines and α-defensins, which may modulate acquired immune responses. During the acute phase of infection, IL-10 correlated positively with viral load and negatively with CD4+T cell counts. Furthermore, α-defensins production was directly correlated with plasma viral RNA, particularly at peak of viral load. When the effects of the MHC were analyzed, a significant association between lower anti-Env binding and neutralizing antibody levels with class IB M4 haplotype and with class IA, IB M4 haplotype, respectively, was observed in the post-acute phase. Lower antibody responses may have resulted into a poor control of infection thus explaining the previously reported lower CD4 T cell counts in these monkeys. Class II M3 haplotype displayed significantly lower acute and post-acute IL-10 levels. In addition, significantly lower levels of α-defensins were detected in class IA M3 haplotype monkeys than in non-M3 macaques, in the post-acute phase of infection. These data indicate that the MHC could contribute to the delicate balance of pro-inflammatory mechanisms, particularly with regard to the association between IL-10 and α-defensins in lentivirus infection. Our results show that host genetic background, virological and immunological parameters should be considered for the design and interpretation of HIV-1 vaccine efficacy studies.